Melintasi Tantangan Pendidikan Online: Dinamika Dukungan Sosial dan Reduksi Stres Akademik pada Mahasiswa Selama Pandemi COVID-19 - Humaira, Mellya (Happiness: Journal of Psychology and Islamic Science, 2023)
Online learning during the Covid-19 pandemic has led to stress experienced by students worldwide affected by the outbreak. This study aims to examine the level of social support and stress in academic activities, as well as to investigate the influence of social support on the level of academic stress during online learning. The research follows a quantitative correlational approach, with a population of 410 students and a sample size of 41 from the Psychology Department at State University of Padang Campus V, Bukittinggi. Data were collected using a questionnaire with a Likert scale distributed via Google Forms. Academic stress was measured using the Educational Stress Scale for Adolescents (ESSA) developed by Sun et al., while Sarafino and Smith's theory was employed to measure the variable of social support. Data were analyzed using simple regression analysis with the assistance of SPSS version 16. The results showed a moderate level of social support and moderate levels of stress. The regression analysis revealed no significant influence of social support on academic stress during online learning for Psychology students at State University of Padang during the Covid-19 pandemic, with a significance value of 0.249; p>0.05. Several factors influencing these results include coping strategies, social conditions, and individual factors.